Cohesion in Arabic Subtitling - Al Omar, Hafsa A. (2016)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Hafsa A. Al Omar entitled, "Cohesion in Arabic Subtitling," submitted in December 2016. Thesis advisor is Dr. Sattar Izwaini. Soft and hard copy available.